Analysis of Internal Customer Satisfaction Related to the Service of the Medical Record at Muhammadiyah Public Hospital Ponorogo - Etik Mardyantari; Sandu Siyoto; Sentot Imam Suprapto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
The medical record department is one of the most important parts in the hospital's effort to provide excellent service to patients. The medical records section is indeed a part that is not directly involved in patient care, but other health workers need a medical record section in order to serve patients. The purpose of this study was to analyze internal customer satisfaction related to the service of the medical records department at Muhammadiyah Hospital Ponorogo. The research design used a descriptive quantitative research design. The sampling technique used was snowball sampling. The results showed that several obstacles were found, namely the speed of providing medical records, the accuracy of providing medical records, the management of KLPCM (Incomplete Filling Of Medical Records) and medical record officers who had medical record competence were still very limited. Improved services provided by the medical record department can increase internal customer satisfaction, and of course will have a direct impact on service to patients. nurses and hospital BPJS healthcare officers.